2020
DOI: 10.1088/1361-6641/ab6bb4
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of Au/n-type InP Schottky barrier diode with monolayer graphene interlayer

Abstract: Au/graphene/n-InP Schottky barrier diode (SBD) was fabricated by the use of spray pyrolysis technique with a monolayer graphene interlayer, and the temperature dependent characteristics was performed in a wide temperature range from 60 to 300 K with steps. The Au/GR/n-InP SBD exhibited excellent rectifying behavior however barrier height (Φ b0 ) of the device increased with increasing temperature while ideality factor (n) and series resistance (R s ) decreased. The strong temperature dependency of SBH and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The Schottky diode parameters such as the ideality factor, BH, saturation current, and Richardson constant can be obtained from the classical method of analyzing the experimental I–V characteristics. [ 23,24 ] Particularly, the ideality factor and the BH are determined from the general equation of the current transport density which is usually described within the well‐known thermionic emission (TE) theory given in Equation () [ 23 ] I=I0exp(qVnkT)[ 1exp(qVkT)]where I 0 is the saturation current determined from extrapolating the linear region of the I–V plots and defined byI0=AA* T2 exp (qnormalΦb0kT)where n is the ideality factor which is dimensionless, V is the applied bias voltage, q is the electronic charge, k is the Boltzmann constant ( k = 8.625 × 10 −5 eV K −1 ), T is the absolute temperature (Kelvin), A is the rectifier contact area ( r = 0.25 mm), A * is the effective Richardson constant (9.4 A cm −2 K −2 for n‐type InP), [ 25,26 ] and Φ b 0 is the experimental apparent BH. From Equation (), it can be written asnormalΦb0=kTqln(AA*T2I0)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Schottky diode parameters such as the ideality factor, BH, saturation current, and Richardson constant can be obtained from the classical method of analyzing the experimental I–V characteristics. [ 23,24 ] Particularly, the ideality factor and the BH are determined from the general equation of the current transport density which is usually described within the well‐known thermionic emission (TE) theory given in Equation () [ 23 ] I=I0exp(qVnkT)[ 1exp(qVkT)]where I 0 is the saturation current determined from extrapolating the linear region of the I–V plots and defined byI0=AA* T2 exp (qnormalΦb0kT)where n is the ideality factor which is dimensionless, V is the applied bias voltage, q is the electronic charge, k is the Boltzmann constant ( k = 8.625 × 10 −5 eV K −1 ), T is the absolute temperature (Kelvin), A is the rectifier contact area ( r = 0.25 mm), A * is the effective Richardson constant (9.4 A cm −2 K −2 for n‐type InP), [ 25,26 ] and Φ b 0 is the experimental apparent BH. From Equation (), it can be written asnormalΦb0=kTqln(AA*T2I0)…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that BH inhomogeneity has been explained by many current‐transmission mechanisms. [ 25 ] However, it is clear that these explanations are not sufficient. The increase in the ideality factor at low temperatures cannot be explained just by the interface layer thickness or interface conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation